The photographer's guide to Color Efex, Analog Efex Pro, Viveza, Sharpener Pro, and Dfine (Learn by video., 2014)
"This critically-acclaimed interactive training program from Peachpit Press offers exceptional quality high-definition video to teach the fundamentals of Color Efex Pro, Analog Efex Pro, Viveza, Sharpener Pro, and Dfine, a premiere suite of tools from Google's Nik Collection. Including 2 hours of tutorials, this Learn by Video training features instructor and professional photographer Sean Arbabi. In this video, Sean first provides an overview of these five tools, defining each and discussing how they work independently and together to create great images. Sean then goes into detail and works through each plug-in: Color Efex Pro and Viveza are used for color correction, creative color and tonality, retouching and creative effects; Analog Efex Pro is used to create effects that reference vintage and alternative photographic process techniques; Sharpener Pro is used to enhance detail in your images; and Dfine can help significantly reduce noise in low-light images. With this video, you'll see how a 20-year pro uses these tools in the Nik Collection to create beautiful color and tonality in his images, as well as great effects that will give your images added appeal."--Resource description page.